Hypertrophic olivery degeneration following cerebral trauma: a rehabilitation perspective - Jing Zhou; Yali Liu; Sayed Zulfiqar Ali Shah (Journal of the Pakistan Medical Association, 2021)
Abstract Hypertrophic olivary degeneration is a kind of trans-synaptic degeneration, caused by the interruption of dentato rubro olivary pathway. Magnetic resonance imaging (MRI) has been the best modality to show the signals of olivary nucleus hypertrophy. It appears on T2?weighted magnetic resonance imaging as hyper-intensities. Here we present a unique case of a 27-year-old male with traumatic brain injury causing multiple intracranial haemorrhages and functional impairment, which was revealed on computerised tomography. Tracheotomy and thoracic drainage were performed immediately. Anti-infection therapy, brain protection, and comprehensive arousal therapy were part of the intervention along with a comprehensive rehabilitation programme including occupational therapy, balance training, coordination, bed mobility training, and strengthening exercises. A holistic diagnostic approach can reduce the chances of misdiagnosing post-traumatic Hypertrophic Olivary Degeneration cases. Continuous...